Desain Komik Matematika Digital Berbasis Budaya berorientasi Literasi dan Resiliensi Matematis - Pika Merliza; Anwaril Hamidy; Uke Ralmugiz; Selvi Loviana; Ahmad Rizal Rifa'i; Mahfud Syaiful (Jurnal Inovasi Matematika, 2026)
Mathematical literacy is an essential competency for students in the 21st century. However, international assessments indicate that Indonesian students’ mathematical literacy remains low, accompanied by limited learning resilience. In response to this issue, culturally contextualized digital learning media are considered relevant to support mathematics learning. This study aims to develop and evaluate the validity and practicality of digital mathematics comics based on cultural contexts, oriented toward mathematical literacy and learning resilience. The study employed a research and development (R&D) approach adapted from the 4-D model, limited to the define, design, and develop stages. Data were analyzed descriptively based on expert validation and user responses. The results showed that the media expert validation score averaged 80.05, categorized as very valid, while the material expert validation score reached 93.33, also categorized as very valid. In addition, the group trial produced an average score of 78.07, categorized as practical, and the teacher’s response score averaged 81.56, categorized as very practical. These findings indicate that the developed digital mathematics comics meet the criteria of validity and practicality.